Formative Assessment as an Innovative Strategies to Develop ESP Students’ Writing Skills - Dwita Laksmita Rachmawati; Sri Hastari (Universitas Hamzanwadi, 2022)
Most undergraduate students experience summative assessment more than formative. In fact, formative assessment is more constructive than summative assessment, which impacts students’ development. Notwithstanding the benefits, research about the incorporation of formative assessment in the ESP class is somehow rare. This recent research focuses on enacting formative assessment in ESP classes regarding students’ writing skills in Indonesia. The researchers employed a case study research design to investigate how ESP teachers implement formative assessment in their classes. The participants are two EFL teachers who teach Business English subjects and forty students majoring in Economics. The researchers gathered the data from close-ended questionnaires, semi-structured interviews, and class observation. This study revealed that ESP learners were provided with multiple chances to enhance myriad facets of their writing skills and establish a good attitude regarding Business English subjects and formative assessment. Thus, educators are required to implement the formative assessment concept in their classes since the educators’ and learners’ involvement can achieve teaching and learning improvement and reflection. Future research should focus on the more particular aspects of formative evaluation, like how to give feedback and classroom discourse, which are equally useful in teaching writing.